2014
DOI: 10.1021/jz500364g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Decay of Thymine Triplets in DNA Single Strands

Abstract: The decay of triplet states and the formation of cyclobutane pyrimidine dimers (CPDs) after UV excitation of the all-thymine oligomer (dT)18 and the locked dinucleotide TLpTL were studied by nanosecond IR spectroscopy. IR marker bands characteristic for the CPD lesion and the triplet state were observed from ∼1 ns (time resolution of the setup) onward. The amplitudes of the CPD marker bands remain constant throughout the time range covered (up to 10 μs). The triplet decays with a time constant of ∼10 ns presum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 46 publications
(81 reference statements)
6
83
0
2
Order By: Relevance
“…In particular it was found that under UVC irradiation direct excitation of thymine bases in TT sequences is the major pathway forming CPD lesions within 1 ps via a singlet excited state . Population of the triplet state via intersystem crossing can also yield CPD lesions but is limited by the overall triplet yield on the order of 0.01 and a comparatively small quantum yield for dimerization to occur from this state …”
Section: Introductionmentioning
confidence: 99%
“…In particular it was found that under UVC irradiation direct excitation of thymine bases in TT sequences is the major pathway forming CPD lesions within 1 ps via a singlet excited state . Population of the triplet state via intersystem crossing can also yield CPD lesions but is limited by the overall triplet yield on the order of 0.01 and a comparatively small quantum yield for dimerization to occur from this state …”
Section: Introductionmentioning
confidence: 99%
“…This matches our recent findings that the triplet excited thymine in (dT) 18 exhibits a lifetime of 10 ns and decays via the formation of a biradical and not via a CT state. 25 In a recent quantum chemical study, CT states between thymine bases have been discussed to be the starting point for the formation of the (6-4) lesion. 17 The decay of such a charge transfer state was predicted to yield oxetane intermediates, as precursors of the (6-4) adduct.…”
mentioning
confidence: 99%
“…In Fig. 7a, b, the values of the C 6 -C 6 0 and C 5 -C 5 0 distances and average angle formed by the velocity vectors of the atoms C 5 and C 5 0 with the C 5 -C 5 0 vector (h 5 and h 5 0 ), and by the velocity vectors of the atoms C 6 and C 6 0 with the C 6 -C 6 0 vector (h 6 and h 6 0 ), are plotted at the moment of the 3 BR/S 0 transition. Those trajectories that underwent dimerization are represented by green pentagons.…”
Section: Resultsmentioning
confidence: 99%
“…This photolesion, which can take place in both the singlet and triplet manifolds, has been extensively investigated spectroscopically [2][3][4][5][6][7] and computationally [8][9][10][11][12][13][14][15]. The triplet pathway is a much slower process [7] and exhibits a smaller yield [6,16] than the singlet mechanism due to inefficient intersystem crossing. As a consequence, this pathway yields very weak spectroscopic signals that preclude unambiguous statements regarding the mechanism [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation